SENYAWA TURUNAN FENOL DARI KULIT BATANG ARTOCARPUS ROTUNDA - Ruhiat, Rosna
Artocarpus rotunda ( Moraceae) have been known to contain phenolic compounds. Previous work on the root bark of the plant had isolated a number of prenylated flavones. This project aims to study further the similar compounds containing in the tree bark part of the plant. The results of the experiments showed that the tree bark contained prenylated flavones artonin E and cycloartobiloxanthone. The structures of these compounds were determined on the basis of spectroscopic data, including UV and IR and also by comparison with the standard compounds. The presence of both compounds in the tree bark implicated that the component of prenylated flavones in the tree root barks are not significantly difference.